Impact of therapeutic drug monitoring of antiretroviral drugs in routine clinical management of patients infected with human immunodeficiency virus and related health care costs: a real-life study in a large cohort of patients - Perrone V; Cattaneo D; Radice S; Sangiorgi D; Federici AB; Gismondo MR; Medaglia M; Micheli V; Vimercati S; Pallone E; Degli Esposti L; Clementi E (Dove Medical Press, 2014)
Valentina Perrone,1 Dario Cattaneo,1 Sonia Radice,1 Diego Sangiorgi,2 Augusto B Federici,3 Maria Rita Gismondo,4 Massimo Medaglia,5 Valeria Micheli,4 Stefania Vimercati,5 Enza Pallone,6 Luca Degli Esposti,2 Emilio Clementi1,71Unit of Clinical Pharmacology, Department of Biomedical and Clinical Sciences, L Sacco University Hospital, University of Milan, Milan, 2CliCon Srl, Health, Economics and Outcomes Research, Ravenna, 3Hematology and Transfusion Medicine, Department of Clinical Sciences and Community Health, 4Clinical Microbiology Virology and Diagnosis of Bioemergency, 5Pharmaceutical Department, 6Quality Clinical Risk and Accreditation Unit, L Sacco University Hospital, Milan, 7Scientific Institute, IRCCS Eugenio Medea, Bosisio Parini, Lecco, ItalyBackground: Highly active antiretroviral therapy (HAART) has reduced morbidity and mortality in patients infected with human immunodeficiency virus (HIV). Studies have documented high interindividual variability in the pharmacokinetics of antiretroviral drugs, which may impair the success of HAART if not managed properly. Therapeutic drug monitoring (TDM) is a useful diagnostic tool that helps clinicians to optimize drug doses so that drug concentrations associated with the highest therapeutic efficacy are obtained with a reduced risk of concentration-dependent adverse effects. The aim of this study was to assess whether use of TDM improves clinical outcomes and cost of illness.Methods: A retrospective cohort study was conducted at L Sacco University Hospital in Milan, Italy, in HIV-infected patients aged ≥18 years with at least one prescription of antiretroviral drugs for which TDM was applied. The inclusion period was from January 2010 to December 2011, with a follow-up period of up to 12 months. Laboratory and administrative databases were analyzed and matched with each other.Results: The cohort consisted of 5,347 patients (3,861 males and 1,486 females) of mean age 43.9±12.5 years. We found that TDM had been used in 143 of these patients, among whom adherence with therapy was significantly higher than among those in whom TDM had not been used (94% versus 78%). In TDM-controlled patients, the mean length of HIV-related hospitalization stay and mean cost of hospitalization were significantly reduced with respect to those observed in the group in which TDM had not been used (7.21 days versus 29.47 days and €293 versus €688, respectively).Conclusion: Inclusion of TDM as part of routine clinical optimization of drug dosing in HIV-infected patients is associated with higher adherence to therapy, reduced length of hospitalization stay, and reduced cost of illness.Keywords: human immunodeficiency virus, therapeutic drug monitoring, health care costs